1996
DOI: 10.1046/j.1471-4159.1996.67020880.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Cerebrospinal Fluid‐Borne Amyloid β‐Peptide: Rapid Clearance into Blood and Appreciable Accumulation by Cerebral Arteries

Abstract: In Alzheimer's disease, the neuritic or senile amyloid plaques in hippocampus and association cortex, the diffuse plaques in brain areas such as the cerebellum and sensorimotor cortex, and the amyloid deposits in the walls of pial and parenchymal blood vessels are mainly composed of amyloid β‐peptides. In the present study, either soluble 40‐residue amyloid β‐peptide radiolabeled with 125I (I‐sAβ) or [14C]polyethylene glycol ([14C]‐PEG, a reference material) was briefly infused into one lateral ventricle of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
142
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(155 citation statements)
references
References 10 publications
12
142
1
Order By: Relevance
“…In addition, animal experiments have shown that, after intracranial or intravenous infusion of 125 I-labelled Aβ, radioactivity is subsequently detected in the kidney and urine 23,110 . These findings indicate that the kidney might participate in physiological clearance of Aβ by filtering Aβ from blood to urine.…”
Section: Renal Dysfunctionmentioning
confidence: 99%
“…In addition, animal experiments have shown that, after intracranial or intravenous infusion of 125 I-labelled Aβ, radioactivity is subsequently detected in the kidney and urine 23,110 . These findings indicate that the kidney might participate in physiological clearance of Aβ by filtering Aβ from blood to urine.…”
Section: Renal Dysfunctionmentioning
confidence: 99%
“…18 While an exact pathophysiological link between AD and NPH is not known, one explanation might rest on altered CSF dynamics resulting in pathologic accumulation of β-amyloid in the brain. 6,20 Investigators have also noted that NPH as a single entity may be quite rare and that an AD-NPH syndrome may manifest as a result of coexisting NPH and AD pathology. 4,15,20 Idiopathic NPH seems to involve an underlying pathophysiology wide in scope, one that ranges from hemodynamic disturbance to major cerebral parenchymal changes.…”
Section: Discussionmentioning
confidence: 99%
“…An alteration of choroid plexus vascular and epithelial morphology, a decrease in choroidal synthesis and transport capacity, and a decrease in CSF secretion is observed in aging, and is exacerbated in Alzheimer's disease [132,134]. The CSF circulation plays a role in amyloid beta distribution and clearance from the brain [49]. An impaired drainage of the brain induced by a decreased CSF secretion may, therefore, favor amyloid deposition.…”
Section: Csf Secretionmentioning
confidence: 99%